Summary of the trigger systems of the Large Hadron Collider experiments ALICE, ATLAS, CMS and LHCb - Albrecht, Johannes; Bozianu, L; Calefice, L; Cella, S; Cocha Toapaxi, Carlos; Doglioni, C; Gligorov, V V; Gooding, J A; Iversen, K E; Inkaew, P; Magdalinski, D; Sopasakis, A; et al. (Journal of physics. G, Nuclear and particle physics, 2025)
In modern high energy physics (HEP) experiments, triggers perform the important task of selecting, in real time, the data to be recorded and saved for physics analyses. As a result, trigger strategies play a key role in extracting relevant information from the vast streams of data produced at facilities like the large hadron collider (LHC). As the energy and luminosity of the collisions increase, these strategies must be upgraded and maintained to suit the experimental needs. This whitepaper presents a high-level overview and reviews recent developments of triggering practices employed at the LHC. The general trigger principles applied at modern HEP experiments are highlighted, with specific reference to the current trigger state-of-the-art within the ALICE, ATLAS, CMS and LHCb collaborations. Furthermore, a brief synopsis of the new trigger paradigm required by the upcoming high-luminosity upgrade of the LHC is provided. This whitepaper, compiled by Early Stage Researchers of the SMARTHEP network, is not meant to provide an exhaustive review or substitute documentation and papers from the collaborations themselves, but rather offer general considerations and examples from the literature that are relevant to the SMARTHEP network.
Gesehen am 04.08.2025